2017
DOI: 10.1111/bld.12210
|View full text |Cite
|
Sign up to set email alerts
|

Improving services for people with learning disabilities and dementia: Findings from a service evaluation exploring the perspectives of health and social care professionals

Abstract: Accessible summary• Dementia is an illness caused by damage to a person's brain.• People with learning disabilities, especially people with Down's Syndrome, are more likely to get dementia, and when they are younger.• We talked to people working in community learning disability teams to find out what they thought about services and support for people with learning disabilities and dementia and carers.• Screening and assessments mean that people get diagnosis and support more quickly and other problems are pick… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 38 publications
1
37
0
Order By: Relevance
“…Building on previous qualitative research (Chapman et al, 2018;Jenkins et al, 2008), this study has drawn on the experiences of both healthcare professionals and carers, to provide a more holis- (Kitwood, 1997) and implement adaptations to ensure a more dementia-friendly home (Strydom, Al-Janabi, Houston, & Ridley, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Building on previous qualitative research (Chapman et al, 2018;Jenkins et al, 2008), this study has drawn on the experiences of both healthcare professionals and carers, to provide a more holis- (Kitwood, 1997) and implement adaptations to ensure a more dementia-friendly home (Strydom, Al-Janabi, Houston, & Ridley, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The little amount of research which has explored IDDCP services and supports has illustrated their usefulness for carers, who are able to access support and training (Chapman, Lacey, & Jervis, 2018; Jenkins et al, 2008); though uptake of training has been reported as low for family carers (Chapman et al., 2018). IDDCP teams can be integral to ending the uncertainty carers and people with an intellectual disability and dementia experience without a diagnosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multidisciplinary teams in the facilities of social services focus on ensuring help in the care of one's self, and activate and support clients in all life areas, e.g. claiming their rights and promoting their interests (Chapman et al, 2018).…”
Section: Residential Facilities Of the Social Services For Seniorsthementioning
confidence: 99%
“…The cited report included stark warnings about difficulties in retaining an ageing health care population, workers taking other jobs, and failure to recruit and keep young people in the sector. At the same time there are growing needs for social care to support primary health care, especially for the elderly (Soares et al, 2018), as well as clients with chronic disease and/or critical social situations (Chapman et al, 2018). High turnover intentions were identified in the decreased interest of new health care workers to keep their demanding work.…”
Section: J O U R N a L P R E -P R O O F Introductionmentioning
confidence: 99%